Web AI in education interactive web-based tutor for self-directed learning - Lubis, Febri Ananda; Rambe, Rizky Rahman; Karim, Abdul; S.Kom, M.TI (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Web AI in Education: Interactive Web-Based Tutor for Self-Directed Learning is an innovative educational platform that leverages artificial intelligence to provide personalized learning experiences. This AI-driven tutor is designed to assist students in learning at their own pace, adapting to different learning styles, and offering real-time feedback. The platform bridges the gap between traditional classroom settings and self-directed learning, allowing students to take control of their educational journey. By utilizing advanced natural language processing models, the tutor can offer tailored explanations, answer questions, and provide constructive feedback. The platform’s accessibility anytime, anywhere, makes it a flexible learning resource suitable for various educational levels. Additionally, it eliminates geographical and financial barriers, promoting equal access to quality education. With its potential for commercialization, the platform offers scalable solutions for educational institutions, tutoring centers, and corporate training programs. This project contributes to the development of personalized learning tools and encourages a culture of entrepreneurship in the education sector